Analysis of Natural Diamonds by Rutherford Backscattering; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 13, iss. 4 - Sokhoreva V. V. Valentina Viktorovna; Malyutin V. M. Vasiliy Mikhailovich; Kashkarov E. B. Egor Borisovich; Kuznetsov S. I. Sergey Ivanovich (2019, 2019)
Title screen